Indonesian registry on atrial fibrillation (OneAF). Issue 19 (14th May 2021) - Raharjo, Sunu Budhi; Chandranegara, Agung Fabian; Hanafy, Dicky Armein; Yamin, Muhammad; Rasyid, Hauda El; Haryadi,; Rizal, Ardian; Ardhianto, Pipin; Hermanto, Dony Yugo; Yuniadi, Yoga
Abstract: Background: Data on the optimal therapeutic international normalized ratio (INR) for non-valvular and valvular atrial fibrillation (AF) in Indonesia is currently unavailable. Therefore, we designed the Indonesian Registry on Atrial Fibrillation (OneAF) registry in order to seek a safe and beneficial range of INR in Indonesian patients with non-valvular and valvular AF. Methods/design: The OneAF registry is a nationwide collaboration of the Indonesian Heart Rhythm Society (InaHRS) enrolling all hospitals with cardiac electrophysiologists in Indonesia. It is a prospective, multicentre, nationwide, observational study aiming to recruit non-valvular and valvular AF patients in Indonesia. The registry was started in January 2020 with a planned 2 years of recruitment. There are 2 respondents for this registry: non-cohort and cohort respondents. Non-cohort registry respondents are AF patients at hospitals who fulfill inclusion and exclusion criteria but did not consent for a 24 month follow up. Whereas patients who consented for a 24 month follow up were included as cohort registry respondents. Key data collected includes basic sociodemographic information, symptoms and signs, medical history, results of physical examination and laboratory test, details of diagnostics and treatment measures and events. Results: Currently, a total of 1568 respondents have been enrolled in the non-cohort registry, including 1065 respondents with non-valvular AF (67.8%) and 503 respondents with valvular AF (32.2%). We believe that the OneAF registry will provide insight into the regional variability of anticoagulant treatment for AF, the implementation of rhythm/rate control approaches, and the clinical outcomes concerning cardiocerebrovascular events. Trial registration: Registered at clinicaltrials.gov (NCT04222868).